The work of French surgeons in disseminating obstetrics in the Polish-Lithuanian Commonwealth in the 18th century - Parent, Arnaud (Acta medica Lituanica, 2013)
In the second half of the 18th century giving birth was a perilous process in the Polish-Lithuanian Commonwealth, partly since obstetrics was not yet a recognised subject. The abolition of the Jesuit Order, which was quite influential in the field of education, provided a good opportunity to reassess the Commonwealth’s educational system. As a result, the Commission of National Education was created, leading to major reforms, especially in the field of medicine. However, because of the lack of specialists in the Commonwealth, it was necessary to search for teachers abroad. Obstetrics was already well developed at that time in France, and the French physicians Pierre Maignan and Nicolas Regnier distinguished themselves by disseminating this science in the Commonwealth. Pierre Maignan was the first person to teach obstetrics at the School of Surgery in Warsaw. But more is known about Nicolas Regnier. In 1775, thanks to his efforts, the first department of childbirth in Lithuania was established, and in 1781 he took charge of the departments of the theory of medicine and obstetrics at the School of Medicine in Vilnius. His lessons demonstrate the knowledge and practices of surgery and obstetrics in the last quarter of 18 century. Pierre Maignan and Nicolas Regnier were pioneers in obstetrics in the Commonwealth. Moreover, they were a good example of the fertile scientific cooperation between France and Poland-Lithuania in the 18th century.